Study on corrosion mechanism of high-nitrogen steel laser-arc hybrid welded joints - Di Bai; Zhikun Yang; Mingying Chen; Hong Zhang; Fengde Liu; Genzhe Huang; Li Yang (Materials Research Express, 2020)
In this paper, the electrochemical microcorrosion behavior of High-nitrogen steel hybrid weld joints with different wires addition were investigated. Polarization curves measurement was conducted to evaluate the corrosion feature in 3.5% NaCl solution. Scanning electron microscopy (SEM) and x-ray diffraction (XRD) were used to analyze the specific corrosion behavior and pitting deepening mechanism induced by precipitated ferrite-dendrites. The experimental results showed that the addition of nitrogen-containing welding wire improved the corrosion resistance of whole weld joint. As a transitional region, the HAZ exhibited relative weak pitting resistance and severe shedding behavior. The coherent dendrites and similar complex geometries led to the accumulation of continuous corrosion channels. The XPS spectra results indicated that the additional nitrogen in the welding wire optimized oxide composition of the surface passive film.